Discontinuation rates of menopausal hormone therapy among postmenopausal women in the post-WHI study era. (3rd September 2015) - Kyvernitakis, I.; Kostev, K.; Hars, O.; Albert, U-s.; Hadji, P.
Abstract: Objectives Many women are reluctant to take menopausal hormone therapy (MHT) and discontinue the treatment within 12 months. The aim of this study was to investigate the persistence rates of combined MHT in the last decade, reflecting changes in the post-Women's Health Initiative era. Methods We analyzed 17 020 patients receiving combined MHT from 2004 to 2013 using the Disease Analyzer database. Results After 12 months of follow-up, 44.6% and 33.5% of patients receiving 1 mg and 2 mg, respectively, of oral combined MHT were still on treatment ( p < 0.0001). The persistence rate of patients receiving < 50 μg of transdermal MHT was 39.1% after 1 year of treatment and presented no differences compared to patients receiving ≥ 50 μg of transdermal MHT with a persistence rate of 38.2%. MHT start in the years 2007–2009 was associated with higher discontinuation rates (hazard ratio 1.04, p = 0.0709) than MHT start in the years 2010–2013 (hazard ratio 0.90, p = 0.0001). Conclusions Our results indicate that patients beginning their treatments in the years 2010–2013 were more treatment-persistent than patients beginning with MHT in the early years after publication of the Women's Health Initiative study (2004–2009). Administration of low-dose oral MHT and transdermal MHT is associated with increased persistency compared to higher doses of oral MHT.